Moderasi Beragama: Praksis Kerukunan Antar Umat Beragama - Prakosa, Pribadyo (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
The Indonesian state has religious pluralism, therefore an effort is needed to maintain inter-religious harmony. One of them is through religious moderation. The principle of religious moderation is to be balanced on two things, namely understanding religious texts (holy books) that must be in accordance with the context, and upholding humanity as the core of religion itself. Christians in Indonesia, both individuals and church institutions need to take part in living religious moderation. The purpose of this research is to describe and analyze the understanding and practice of religious moderation at church. One of them is at Gereja Kalimantan Evangelis (GKE), namely GKE Kasongan, Katingan Regency, sentral Kalimantan Province. The method used is a qualitative method with a descriptive-analytical approach. Sources of data from interviews and literature review on religious moderation. The results show that although most of the members of the GKE Kasongan do not understand the term religious moderation, in practice it has been realized. It is necessary to socialize and realize religious moderation which can be started from each religious community in Indonesia. Negara Indonesia memiliki kemajemukan agama, oleh sebab itu diperlukan suatu upaya untuk memelihara kerukunan antar umat beragama. Salah satunya adalah melalui moderasi beragama. Prinsip moderasi beragama yakni seimbang pada dua hal yakni memahami teks (kitab suci) keagamaan harus sesuai dengan konteks, dan menjunjung kemanusiaan sebagai inti dari beragama itu sendiri. Umat kristen di Indonesia, baik individu maupun institusi gereja perlu ambil bagian dalam menghidupi moderasi beragama. Tujuan Penelitian adalah mendeskripsikan dan menganalisa pemahaman dan praksis moderasi Beragama di gereja. Salah satunya adalah di Gereja Kalimantan Evangelis (GKE) yakni GKE Kasongan, Kabupaten Katingan, Provinsi Kalimantan Tengah. Metode yang digunakan adalah metode kualitatif dengan pendekatan deskriptif-analitis. Sumber data dari hasil wawancara dan kajian literatur tentang moderasi beragama. Hasil Penelitian menunjukkan sekalipun sebagian besar Jemaat GKE Kasongan belum memahami istilah moderasi beragama namun praksis moderasi beragama sudah diwujudkan, sehingga perlu disosialisasikan dan diwujudkan dalam hal pemahaman maupun praksis yang dimulai dari masing-masing komunitas umat beragama di Indonesia.